Estrategia para el desarrollo sustentable del ecosistema de emprendimiento cultural y creativo - Hernández Acosta, Javier J. (Editorial Uniagustiniana, 2018)
This chapter seeks to further discuss cultural policies for the creative economy beyond the initial exercises of promotion and awareness creation. The paper em-phasizes on an approach to the future that allows taking the necessary actions for sustainable development in these sectors with great potential for economic, social and cultural impact. As an exploratory study, from the analysis of contents and case studies, it recognizes the limitations of its scope,, however, it is proposed as a starting point for a broad and diverse research agenda for the issue in Latin American countries, whether in the local, regional or national level. Based on three interna-tional models and the case studies of Puerto Rico, Chile, and Colombia, the chapter proposes the elements that a strategy must have for the development of cultural and creative industries in a territory, including its scope, general and specific objectives, and indicators to ana-lyze its performance.